2016
DOI: 10.2527/jas.2015-9517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium supplementation to feedlot steers on growth performance, insulin sensitivity, and carcass characteristics1

Abstract: Objectives were to determine the effects of chromium propionate supplementation on growth performance, insulin and glucose metabolism, and carcass characteristics of beef cattle. Steers ( = 34) were stratified by BW and assigned to 1 of 2 treatments: 1) no supplemental Cr (Cont) or 2) 3 mg supplemental Cr·steer·d (CrP). Both supplements, Cont and CrP, were delivered via 0.454 kg ground corn top-dressed on the basal diet. There was no effect ( ≥ 0.45) of CrP on ADG, DMI, G:F, or final BW. However, steers fed Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
1
25
1
Order By: Relevance
“…Glucose is then metabolized to regenerate NADPH consumed by the enzyme catalyzation ( Babior, 1984 ). It is well documented that supplemental chromium modulates glucose and insulin metabolism of cattle ( Kegley et al, 2000 ; Swanson et al, 2000 ; Sumner et al, 2007 ; Yan et al, 2008 ; Bernhard et al, 2012a ; Spears et al, 2012 ; Kneeskern et al, 2016 ). Therefore, as chromium aids in glucose uptake, glucose may be more readily available to regenerate the respiratory burst process and potentially improve the immune response of the animal.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose is then metabolized to regenerate NADPH consumed by the enzyme catalyzation ( Babior, 1984 ). It is well documented that supplemental chromium modulates glucose and insulin metabolism of cattle ( Kegley et al, 2000 ; Swanson et al, 2000 ; Sumner et al, 2007 ; Yan et al, 2008 ; Bernhard et al, 2012a ; Spears et al, 2012 ; Kneeskern et al, 2016 ). Therefore, as chromium aids in glucose uptake, glucose may be more readily available to regenerate the respiratory burst process and potentially improve the immune response of the animal.…”
Section: Resultsmentioning
confidence: 99%
“…In cattle, ivGTT is commonly used to test for conditions such as insulin resistance (De Koster and Opsomer, 2013) or determine the levels of insulin sensitivity (Abuelo et al, 2016). The test can also predict changes in nonesterified fatty acids (Boston et al, 2008) and determine the effects of certain diets on energy metabolism (Kneeskern et al, 2016). Furthermore, Pieper et al (2016) found high heritability for some ivGTT traits in young Holstein bulls including GA and GHLT with estimated heritabilities of 0.43 and 0.40, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…LEA is a cross-sectional measurement of the vertebral column of the animal, between Kneeskern et al (2016), which evidenced the need to keep steers supplemented with CrP for longer time in finishing to reach the same degree of finish of the animals not supplemented with the mineral. There was no difference (p> 0.05) in the SFT between the genetic groups, although there was a difference in the FIN scores attributed to the carcasses of these animals.…”
Section: Resultsmentioning
confidence: 99%
“…As it participates in energy metabolism, it is assumed that Cr may influence in the quality of the carcass of the animals (Polizel Neto et al, 2009a), which resulted in research focusing on the supplementation of cattle (Domínguez-Vara Com. Sci., Bom Jesus, v.10, n.2, p.278-285, Apr./Jun. 2019 Kneeskern et al, 2016;Oliveira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%